2010
DOI: 10.1155/2010/253853
|View full text |Cite
|
Sign up to set email alerts
|

Beverage-Specific Alcohol Sale and Cardiovascular Mortality in Russia

Abstract: Objective. Recent research evidence suggests that the consumption of different types of alcoholic beverage may have a differential effect on cardiovascular diseases (CVD) mortality rates. The aim of this study was to examine the relation between the consumption of different beverage types and CVD mortality rates in Russia across the later-Soviet and post-Soviet periods. Method. Age-standardized male and female CVD mortality data for the period 1970–2005 and data on beverage-specific alcohol sales were obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 34 publications
4
35
0
5
Order By: Relevance
“…The pooled effect estimated of 3.9% per litre close to previous findings, obtained for Northern Europe (3% per litre) and stronger than the estimates for Mid-and South-European countries (1% per litre) (Norström, 2001). In this context, it should be pointed out that recent time series analysis based on Russia data showed that the relationship between alcohol and mortality was stronger for sales of distilled spirits relative to the total level of alcohol sale (Razvodovsky, 2010b). Similarly, the large individuallevel study in the Russian Federation found a strong positive association between frequency of drinking vodka/frequency of binge drinking and all-cause mortality (Nicholson, Bobak, Murphy, Rose, & Marmot, 2005).…”
Section: Discussionsupporting
confidence: 80%
“…The pooled effect estimated of 3.9% per litre close to previous findings, obtained for Northern Europe (3% per litre) and stronger than the estimates for Mid-and South-European countries (1% per litre) (Norström, 2001). In this context, it should be pointed out that recent time series analysis based on Russia data showed that the relationship between alcohol and mortality was stronger for sales of distilled spirits relative to the total level of alcohol sale (Razvodovsky, 2010b). Similarly, the large individuallevel study in the Russian Federation found a strong positive association between frequency of drinking vodka/frequency of binge drinking and all-cause mortality (Nicholson, Bobak, Murphy, Rose, & Marmot, 2005).…”
Section: Discussionsupporting
confidence: 80%
“…We used this model specification to estimate the relationship between the time series stroke mortality and alcohol consumption rates in this paper. In line with previous aggregate studies (Norström et al, 2001;Razvodovsky, 2005Razvodovsky, , 2006Razvodovsky, , 2009Razvodovsky, , 2010b, we estimated semi-logarithmic models with logged output. The following model was estimated:…”
Section: Discussionmentioning
confidence: 85%
“…We used this model specification to estimate the relationship between the time series alcohol poisoning mortality and beverage-specific alcohol sales in this paper. In line with previous aggregate studies [17,26,[28][29][30] we estimated semi-logarithmic models with logged output. The following model was estimated:…”
Section: Discussionmentioning
confidence: 94%